2022
DOI: 10.21203/rs.3.rs-2066338/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic Review: Interventions to Quit Tobacco Products for Young Adults

Abstract: Introduction: Young adulthood is an important period for smoking cessation; however, there is limited evidence of smoking-cessation interventions for young adults. The aims of this study were to identify evidence-based smoking-cessation strategies for young adults, examine gaps in the literature regarding smoking cessation among young adults, and discuss methodological issues/challenges related to smoking-cessation studies for young adults. Methods: Studies tested interventions for smoking cessation among youn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Social media is recognized as an engaging platform for behavioral interventions among young adults (Park et al, 2022). Various studies utilizing different types of social media have demonstrated the benefits of using this medium in tobacco control interventions among adolescents and young adults.…”
Section: Resultsmentioning
confidence: 99%
“…Social media is recognized as an engaging platform for behavioral interventions among young adults (Park et al, 2022). Various studies utilizing different types of social media have demonstrated the benefits of using this medium in tobacco control interventions among adolescents and young adults.…”
Section: Resultsmentioning
confidence: 99%